Sleep apnea prevalence in acute myocardial infarction--the Sleep Apnea in Post-acute Myocardial Infarction Patients (SAPAMI) Study - Ludka, Ondrej; Stepanova, Radka; Vyskocilova, Martina; Galkova, Lujza; Mikolaskova, Monika; Belehrad, Milos; Kostalova, Jana; Mihalova, Zuzana; Drozdova, Adela; Hlasensky, Jiri; Gacik, Michal; Pudilova, Lucie; et al. (International journal of cardiology, 2014)
BACKGROUND: While sleep apnea (SA) might be a modifiable cardiovascular risk factor, recent data suggest that SA is severely underdiagnosed in patients after acute myocardial infarction (MI). There is limited evidence about day-night variation of onset of MI on dependence of having SA. We therefore investigated the prevalence of SA and examined the day-night variation of onset of MI in acute MI patients. METHODS: We prospectively studied 782 consecutive patients admitted to the hospital with the diagnosis of acute MI. All subjects underwent sleep evaluations using a portable device after at least 48 h post-admission. Using the apnea-hypopnea index (AHI), groups were defined as patients without SA (<5 events/h), mild SA (5-15 events/h), moderate SA (15-30 events/h), and severe SA (≥ 30 events/h). RESULTS: Almost all patients (98%) underwent urgent coronary angiography and 91% of patients underwent primary PCI. Using a threshold of AHI ≥ 5 events/h, SA was present in 65.7% of patients after acute MI. Mild SA was present in 32.6%, moderate in 20.4% and severe in 12.7%. The day-night variation in the onset of MI in all groups of SA patients was similar to that observed in non-SA patients. From 6 AM to 12 PM, the frequency of MI was higher in both SA and non-SA patients, as compared to the interval from 12 AM to 6 AM (all p<0.05). CONCLUSION: There is a high prevalence of SA in patients presenting with acute MI. Peak time of MI onset in SA patients was between 6 AM and noon, similar to that in the general population. Whether diagnosis and treatment of SA after MI will significantly improve outcomes in these patients remains to be determined.
Keywords: Female; Prevalence; Sleep Apnea Syndromes; ženské pohlaví; Day–night variation; Time Factors; časové faktory; lidé; Acute myocardial infarction; Risk Factors; prevalence; prospektivní studie; Male; Aged; Prospective Studies; Sleep apnea; rizikové faktory; Myocardial Infarction; syndromy spánkové apnoe; lidé středního věku; senioři; mužské pohlaví; Middle Aged; infarkt myokardu; Humans